With or Without You: A Heuristic Approach to Value Multiple Programs Using the Contingent Valuation - Lee, Jongyearn (KDI School of Public Policy and Management, 2024)
We propose a cost-effective and bias-avoiding approach to value multiple programs using the contingent valuation. After eliciting the willingness to pay for a program given all other programs in a package are assumed to be implemented, the approach adopts a value adjustment scheme with which the respondent is given a chance to modify the initial willingness to pay when the package excludes one of other programs. The approach attempts to limit the number of respondents and the number of questions to a respondent to save cost and time, and to reduce the cognitive burden in response for minimizing potential biases, respectively. The proposed approach is applied to a case with six facilities in a complex to find reasonable substitution effects among facilities empirically. The further analysis with value reduction responses also verifies that the respondents' perception on the substitution effect between facilities are economically intuitive. Finally, precautions are listed when using this approach for benefit estimation for the purpose of the cost-benefit analysis in practice.
Keywords: Contingent Valuation Method; Non-use Value; Part-Whole Bias; Multivariate Probit